Co-inoculation of aflatoxigenic and non-aflatoxigenic strains of aspergillus flavus to assess the efficacy of non-aflatoxigenic strains in growth inhibition and aflatoxin b1 reduction - Khan, Rahim; Mohamad Ghazali, Farinazleen; Mahyudin, Nor Ainy; Putra Samsudin, Nik Iskandar (Multidisciplinary Digital Publishing Institute, 2021)
The pre-harvest biocontrol approach currently used includes laboratory inoculations using non-aflatoxigenic strains of Aspergillus flavus. This strategy effectively suppresses the indigenous aflatoxigenic strains and reduces aflatoxin accumulation in sweetcorn. The current in vitro study’s main objective is to determine the diametric growth rates of both Aflatoxin (AF)+ and AF− strains and improve the understanding of competitive relationships among these strains in sweetcorn (Zea mays). Sweetcorn kernels inoculated with AF+ strains only, AF− strains only, and co-inoculated with AF+ + AF− strains were investigated for aflatoxin concentrations. The diametric growth results revealed that growth rates of AF− strains at 25 and 30 °C were much greater than AF+ strains, which was in line with previous studies. The in vitro findings showed that the AKR5− and AKL34− biocontrol strains effectively inhibited the colony propagation and subsequent AFB1 contamination (up to 79%) of AF+ strains. On the other hand, the AKR1− and AKL35− were least effective in reducing AFB1 contents only by 58% and 60%, respectively. There was a significant difference (p < 0.05) in the reduction of AFB1 contents achieved by AF− strains of A. flavus. The findings of the present study indicated the reduction in AFB1 with population expressions of AF+ strains by the AF− strains and supports the notion of competitive exclusion through vigorous development and propagation of the non-aflatoxigenic fungi.